An Investigation into Discourse and Jurisprudence of the Holy Quran’s Translation with an Emphasis on Salfi’s Perspective - m0hammadreza ebrahimnejad (پژوهش نامه معارف قرآنی, 2017)
Islam is a universal religion with a comprehensive and inclusive set of principles, most of which are laid out in the Holy Quran. For non-Arab Muslims, translation is the only way to access those readings. As a result, Muslim scholars have long been dealing with the issue of translation and two opposing views have been formed over time. The universality of Islam arguably makes translation not only permissible, but also necessary. However, other factors such as the spread of the Salafi school of thought has opposed translation. The opponents who are mostly from the Salafi School, have listed up to fifteen reasons, namely the impossibility of translating Quran and the risk of distorting Quran’s statements. This study examines these reasons to challenge them and show that they are baseless and lack the necessary logical foundation.